2021
DOI: 10.1093/mnras/stab2752
|View full text |Cite
|
Sign up to set email alerts
|

Metal-enriched halo gas across galaxy overdensities over the last 10 billion years

Abstract: We present a study of metal-enriched halo gas traced by Mg ii and C iv absorption at z < 2 in the MUSE Analysis of Gas around Galaxies survey and the Quasar Sightline and Galaxy Evolution survey. Using these large and complete galaxy surveys in quasar fields, we study the dependence of the metal distribution on galaxy properties and overdensities, out to physical projected separations of 750 kpc. We find that the cool, low-ionization gas is significantly affected by the environment across the full redsh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 182 publications
(306 reference statements)
18
31
0
Order By: Relevance
“…A similar declining trend is well-known in the CGM literature for decades (e.g., Lanzetta & Bowen 1990;Chen et al 2010;Nielsen et al 2018;Dutta et al 2021). Adopting the relation presented in Dutta et al (2021) we obtained galactocentric distances of 200 − 300 kpc for the Mg ii REW we measured from the stacked profiles, provided that the absorption signal is dominated by the CGM of cluster galaxies. To quantify the possible contribution from the CGM of cluster galaxies, we excluded 12, 217 pairs from our analysis for which at least one galaxy is detected within 300 kpc radius centred on the background quasar with a photometric or spectroscopic redshift consistent with the cluster redshift within ±1000 km s −1 7 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar declining trend is well-known in the CGM literature for decades (e.g., Lanzetta & Bowen 1990;Chen et al 2010;Nielsen et al 2018;Dutta et al 2021). Adopting the relation presented in Dutta et al (2021) we obtained galactocentric distances of 200 − 300 kpc for the Mg ii REW we measured from the stacked profiles, provided that the absorption signal is dominated by the CGM of cluster galaxies. To quantify the possible contribution from the CGM of cluster galaxies, we excluded 12, 217 pairs from our analysis for which at least one galaxy is detected within 300 kpc radius centred on the background quasar with a photometric or spectroscopic redshift consistent with the cluster redshift within ±1000 km s −1 7 .…”
Section: Discussionsupporting
confidence: 82%
“…We find a decreasing trend between Mg ii REW and ρ cl and ρ cl /R 500 , likely due to lower density, metallicity, and covering fraction of cool gas at large radii (Emerick et al 2015;Butsky et al 2019). A similar declining trend is well-known in the CGM literature for decades (e.g., Lanzetta & Bowen 1990;Chen et al 2010;Nielsen et al 2018;Dutta et al 2021). Adopting the relation presented in Dutta et al (2021) we obtained galactocentric distances of 200 − 300 kpc for the Mg ii REW we measured from the stacked profiles, provided that the absorption signal is dominated by the CGM of cluster galaxies.…”
Section: Discussionsupporting
confidence: 80%
“…An effect that has been noted in the literature is that galaxies with neighbors have detectable absorption in ions including Mg II and O VIout to greater distances than galaxies without neighbors (Johnson et al 2015;Dutta et al 2021). We see this more extended O VI around galaxies with neighbors in CGM 2 as well.…”
Section: The Influence Of Galaxy Environmentsupporting
confidence: 76%
“…Similarly, recent radio observations with the Very Large Array (VLA) have revealed a large amount of neutral hydrogen (H ) in the Virgo cluster, mostly stripped from cluster galaxies due to rampressure of hot ICM (Vollmer et al 2012;Bahé et al 2013). In addition to H , observations have also revealed the presence of cool low-ionization gas (e.g., Mg ) in groups and clusters (Fossati et al 2012;Dutta et al 2020;Hamanowicz et al 2020;Dutta et al 2021b) and submillimeter observations have also revealed long extended filaments of cold molecular gas in cool-core clusters (Edge 2001). In a recent paper (Olivares et al 2019), the authors analysed ALMA (CO lines) and MUSE (H𝛼) data of three clusters: Centaurus, Abell S1101, and RXJ1539.5 and detected long (3-25 kpc) extended molecular gas filaments in the inner part of cluster halo.…”
Section: Introductionmentioning
confidence: 93%
“…Idealized simulations of gas in the ICM have shown that cold gas can form in-situ out of hot ICM due to local temperature fluctuations and thermal instabilities (TI), if the ratio of thermal instabilities time-scale to the free-fall time-scale is below some critical threshold (𝑡 TI /𝑡 ff 10) (Sharma et al 2012;McCourt et al 2012;Voit & Donahue 2015;Voit et al 2017). Besides the in-situ formation of cold gas in clusters (Dutta et al 2021a), other phenomena such as interactions between cluster galaxies (Wang 1993) and ram pressure stripping (Gunn & Gott 1972) of cold gas from satellite galaxies (Cortese et al 2007;McCarthy et al 2008;Yun et al 2019) can also give rise to cold gas in clusters. Therefore, it is important to explore the nature of cool low-ionization gas in cluster environments and compare its incidence and physical properties with cool gas surrounding isolated galaxies in order to understand its origin and impact on galaxy evolution.…”
Section: Introductionmentioning
confidence: 99%